GENERASI ALPHA – TUMBUH DENGAN GADGET DALAM GENGGAMAN - Ria Novianti; Hukmi Hukmi; Ilga Maria (Program Studi Pendidikan Guru PAUD Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2019)
The general objective in this study was to determine the description of the use of devices in alphageneration children in Pekanbaru City. The gadget comes from English which means small electronic devices that havespecial functions. Among smartphones like the iPhone and Blackberry, and netbooks (a combination of portablecomputers such as notebooks and the internet). In Indonesian the word gadget is often also referred to as a gadget.This research was conducted in Pekanbaru City in 12 Districts. The results of the study explained that the gadget devicesthat children use are still borrowing parents, the type of gadget that children use the most is smartphones, the activitiesthat children do other than using gadgets most often are playing outside the home, the places where children use themost gadgets use the family room , the time to use the gadget for children is not every day, namely on certain days suchas holidays, the application that is often used by children is Youtube, complaints from children after using the gadgetare raging if not given a gadget, and accounts that most children have are YouTube channels.